Synthesis and Preliminary Pharmacological Evaluation of Some New Triazole Derivatives (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
On the basis of the results which was previously obtained from the structural and the theoretical studies on -adrenergic drugs, a series of 2-propanolamine derivatives containing triazole moiety have been prepared and evaluated for their cardiovascular activity . These derivatives were tested by using spontaneously-beating right atria of albino rats.